Strategies for leaching and agricultural use of saline lands under conditions of water shortage - Shirokova Yulia; Paluashova Gauharay; Sadiev Farkhod; Kodirov Dilshod; Juraeva Nargiza (E3S Web of Conferences)
An analysis of the authors' experimental data on land leaching from salinization was carried out. The regularity of specific water consumption for salt leaching is assessed depending on the degree of soil salinization and negative environmental factors when leaching the soil with a layer of water. It is shown that leaching at high rates reduces soil fertility indices (NPK). The results of studies of alternative innovative methods of soil desalination and agricultural use of lands subject to salinization are presented. Soil desalination technologies that ensure enhanced salt leaching and water savings are considered: leaching against the background of deep soil loosening and the use of a local preparation containing an organic acid. The data of experiments with microbiological preparations produced in Uzbekistan, adapted to soil salinization and ensuring crop yields, are presented.